(untitled) (Baghdad Science Journal, 2021)
Depletion of fossil fuel is one of the main reasons why the bioethanol has become popular. It is a renewable energy source. In order to meet the great demand of bioethanol, it is best that the bioethanol production is from cheap raw materials. Since the golden shower fruit is not being utilized and is considered as waste material, hence, this study was conducted to make use of the large volume of the residue as feedstock to test its potential for bioethanol extraction.The main goal of this study is to obtain the most volume of bioethanol from the golden shower fruit liquid residue by the factors, days of fermentation (3, 5, and 7 days) and sugar concentration (15, 20 and 25 brix) of the liquid residue. Also, part of the study is to compute the cost of production in extracting bioethanol from the golden shower fruit. Each treatment was replicated three (3) times. The Two-Factorial Analysis of Variance (ANOVA) of the Complete Randomized Design (CRD) was used to analyze the treatments. Treatments means were compared using the Duncan’s Multiple Range Test (DMRT).